Indigenous endophyte bacteria ability to control Ralstonia and Fusarium wilt disease on chili pepper - YULMIRA YANTI; WARNITA WARNITA; REFLIN REFLIN; MUNZIR BUSNIAH (Society for Indonesian Biodiversity, 2018)
Yanti Y, Warnita, Reflin, Busniah M. 2018. Indigenous endophyte bacteria ability to control Ralstonia and Fusarium wilt disease on chili pepper. Biodiversitas 19: 1532-1538. Bacterial wilt and Fusarium wilt caused by Ralstonia syzigii subsp. indonesiensis and Fusarium oxysporum f.sp. capsici (Foc), respectively are the most damaging vascular pathogens in chili pepper (Capsicum annuum L.) and many other crops limiting their production, worldwide. Various strategies have been developed to control wilt pathogens including the application of chemical pesticides, which generally considered as the most effective and fastest strategy for plant disease management. However, effective chemicals for wilt pathogens of chili pepper plants are not available, yet. Endophytic bacteria considered as one of options to control vascular wilt disease because of its ability to live and colonize in internal roots of plants. Previous research has been done to select endophytic indigenous bacteria isolates which can promote growth rate of chili pepper. The purpose of the research was to identify the selected indigenous endophyte bacteria isolates acquired from our previous study using 16S rRNA identifications and to screen the selected endophytic indigenous bacteria to control both R. syzigii subsp. indonesiensis and Foc. Results from 16S r RNA analysis showed that all of 9 isolates were identified as Bacillus spp., such as Bacillus cereus ATCC 14579, Bacillus pseudomycoides strain NBRC 101232, Bacillus toyonensis strain BCT-7112, Bacillus thuringiensis strain ATCC 10792, Bacillus weihenstephanensis strain DSM 11821, Bacillus mycoides strain 273, Bacillus cereus strain NBRC 15305, Bacillus bingmayongensis strain FJAT-13831 and Bacillus manliponensis strain BL4-6. Our results showed that most of endophytic bacteria isolates application could control both bacterial and Fusarium wilt diseases. Six out of nine isolates can suppress R. syzigii subsp. indonesiensis without developing any symptoms and five isolates could suppress symptoms of Foc. Isolates Bacillus pseudomycoides strain NBRC 101232 Bacillus thuringiensis strain ATCC 10792 and Bacillus mycoides strain 273 were potential for control Foc and R. syzigii subsp. indonesiensis in chili pepper.